(untitled) (Research, Society and Development, 2026)
Introduction: Speech-language pathology has faced increasing challenges in the face of learning disorders and difficulties, whose high prevalence and impacto n child development require increasingly specialized interventions. Objective: To analyze the application of Applied Behavior Analysis (ABA) strategies in the speech-language pathology context, focusing on the management of escape behaviors exhibited by children with learning difficulties. Methodology: This is a qualitative study in the form of a narrative literature review. The databases SciELO, PubMed, and LILACS were consulted, and articles published between 2020 and 2025 were selected. Descriptors in Portuguese and English were used, obtained from the Health Sciences Descriptors (DeCS) platform: “Applied Behavior Analysis” AND “speech-language pathology” AND “escape behavior” AND “specific learning disorder.” Results and Discussion: The analysis showed that the integration between ABA and Speech-Language Pathology enhances therapeutic outcomes, especially when considering the child’s preference and motivation in the selection of procedures. Conclusion: The use of ABA in the speech-language pathology context not only contributes to the control of escape behaviors but also strengthens the development of communication, learning, and social inclusion, although research gaps still remain regarding learning disorders specifically.